2009
DOI: 10.1021/am900458g
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Grafting of Diamond Nanoparticles: A Versatile Route to Nanocrystalline Diamond Thin Films

Abstract: Nanodiamond (ND) seeding is a well-established route toward the CVD (chemical vapor deposition) synthesis of diamond ultrathin films. This method is based on the deposition onto a substrate of diamond nanoparticles which act as pre-existing sp(3) seeds. Here, we report on a straightforward method to disperse diamond nanoparticles on a substrate by taking advantage of the electrostatic interactions between the nanodiamonds and the substrate surface coated with a cationic polymer. This layer-by-layer deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 49 publications
1
69
0
Order By: Relevance
“…Fullerenes or carbon nanotubes exhibit hydrophobic behavior and their stability in water suspension can only be obtained after their functionalization [178][179][180]. These colloids of NDs in water were also used to obtain homogeneous seeding of substrates for CVD growth of thin diamond films [181,182]. Some groups used surfactants like sodium oleate [98] or oleylamine [183] to improve the colloidal stability of NDs.…”
Section: Solubility Stability In Colloidsmentioning
confidence: 99%
“…Fullerenes or carbon nanotubes exhibit hydrophobic behavior and their stability in water suspension can only be obtained after their functionalization [178][179][180]. These colloids of NDs in water were also used to obtain homogeneous seeding of substrates for CVD growth of thin diamond films [181,182]. Some groups used surfactants like sodium oleate [98] or oleylamine [183] to improve the colloidal stability of NDs.…”
Section: Solubility Stability In Colloidsmentioning
confidence: 99%
“…These polymers are soluble in water. Such layer by layer deposition was previously achieved for other nanoparticles [124,125] and later applied to NDs [126][127][128][129]. Negatively charged NDs were then deposited through a layer by layer process on substrates coated with PDDAC [126].…”
Section: Deposition Of Ndsmentioning
confidence: 99%
“…Recent research 24 has shown that electrostatic grafting (or self-assembly) on surface modified substrates can result in very high ND particle densities by taking advantage of the electrostatic interactions between the ND particles and the substrate surface. Alternatively, by a heat treatment in air, the ND particle surface becomes mainly covered by carboxylic groups and a negative surface charge is obtained when suspended in water.…”
Section: Of 36mentioning
confidence: 99%
“…This is in line with several recent reports that focused on the seeding of ND particles by electrostatic self-assembly. [24][25][26]51,52 Electrostatic grafting on substrates (with or without surface modification) can result in a very high density and uniformity of ND particles if a properly selected surface modification and fractionalization of the ND particles are employed to improve their dispersion and to separate those particles into a more narrow range of particle sizes. 26,52 Ideally, ND particles are anchored to the substrate surface as seeds of single grain size for NCD film growth, but it is well known that the formation of ND particle agglomerates is difficult to avoid.…”
Section: Interactions Between Substrate Surface and Nd Particlesmentioning
confidence: 99%